Envisioning the anthropocene and posthumanism in science fiction and fantasy works: a study of the novels The Windup Girl, The Fifth Season, and short story “Vaster Than Empires and More Slow." - Chowdhury, Iman (BRAC University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2019.